2006
DOI: 10.1002/jqs.1073
|View full text |Cite
|
Sign up to set email alerts
|

Integration of ice‐core, marine and terrestrial records for the Australian Last Glacial Maximum and Termination: a contribution from the OZ INTIMATE group

Abstract: The degree to which Southern Hemisphere climatic changes during the end of the last glacial period and early Holocene (30-8 ka) were influenced or initiated by events occurring in the high latitudes of the Northern Hemisphere is a complex issue. There is conflicting evidence for the degree of hemispheric 'teleconnection' and an unresolved debate as to the principle forcing mechanism(s). The available hypotheses are difficult to test robustly, however, because the few detailed palaeoclimatic records in the Sout… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
50
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(50 citation statements)
references
References 67 publications
(96 reference statements)
0
50
0
Order By: Relevance
“…We adjusted temperature and rainfall to generate two LGM predictions based on: 1) temperature 6 o C lower and rainfall 20% lower and 2) temperature 6 o C lower and rainfall 40% lower. We chose regionally generalised climatic adjustments from approximate sea surface temperature (SST) reconstructions at the LGM (Turney et al 2006; Van der Kaars et al 2006; Barrows et al 2007) and terrestrial and near-shore proxy data (Williams et al 2009). We confined our predictions to the LGM due to the limitations in knowledge of the climate and the physiology of koalas at longer past time frames.…”
mentioning
confidence: 99%
“…We adjusted temperature and rainfall to generate two LGM predictions based on: 1) temperature 6 o C lower and rainfall 20% lower and 2) temperature 6 o C lower and rainfall 40% lower. We chose regionally generalised climatic adjustments from approximate sea surface temperature (SST) reconstructions at the LGM (Turney et al 2006; Van der Kaars et al 2006; Barrows et al 2007) and terrestrial and near-shore proxy data (Williams et al 2009). We confined our predictions to the LGM due to the limitations in knowledge of the climate and the physiology of koalas at longer past time frames.…”
mentioning
confidence: 99%
“…Subsequently, the INTIMATE remit has expanded geographically, to include the whole Atlantic basin and also Australasia (Alloway et al, 2007;Turney et al, 2006), while an extended time scale covers the early Holocene and deeper parts of the Late Quaternary record. An initial expansion of the INTIMATE timeframe back to 30 ka (thousand years before present, present referring to A.D. 1950 unless otherwise indicated) was followed by a further extension to 60 ka .…”
Section: Introductionmentioning
confidence: 99%
“…The method is applied to late Quaternary sedimentary records from the subtropics to cool mid-latitudes to generate mean annual and summer temperature reconstructions. (Alloway et al, 2007;Turney et al, 2007;Reeves et al, 2013;Petherick et al, 2013 Geographically, the distribution of proxy based records is rather sparse and non-uniform in Australia. However, studies Turney et al, 2007;Williams et al, 2009) suggested that Australia can provide high quality information on likely patterns and directions of the future changes in the Southern Hemisphere.…”
Section: Introductionmentioning
confidence: 99%
“…(Alloway et al, 2007;Turney et al, 2007;Reeves et al, 2013;Petherick et al, 2013 Geographically, the distribution of proxy based records is rather sparse and non-uniform in Australia. However, studies Turney et al, 2007;Williams et al, 2009) suggested that Australia can provide high quality information on likely patterns and directions of the future changes in the Southern Hemisphere. Firstly, it covers a large climate range from the cool temperate zone to the tropics and incorporates broad humid, sub-humid, arid and semi-arid zones.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation